The principle of composition and decomposition of properties in modal interpretations of quantum mechanics (Culturas Científicas, 2025)
Modal interpretations of quantum mechanics were developed in the 1980s with the aim of explaining quantum measurement without invoking a collapse of the wave function. One of the key factors that influenced the evolution of these interpretations was their compliance with the principle of composition and decomposition of properties, which establishes the correspondence between the properties of composite systems and those of their subsystems. In several of the earliest modal interpretations, however, this principle is not satisfied. This limitation motivated the development of alternative versions designed to overcome such inadequacy, among them the modal-Hamiltonian interpretation. In this article, we examine the precise sense in which the principle of composition and decomposition of properties fails in certain modal interpretations and how this problem is resolved in others. We also explore whether the restrictions imposed by the modal-Hamiltonian interpretation on its actualization rule can be relaxed without compromising its consistency with the principle.
Keywords: actualization rule; modal interpretations; ontology of quantum mechanics; property composition principle; property decomposition principle